'Endoflip® evaluation of pharyngo‐oesophageal segment tone and swallowing in a clinical population: a total laryngectomy case series'. (April 2015) - Regan, J.; Walshe, M.; Timon, C.; McMahon, B.P.
<x xml:space="preserve">Abstract</x> Objectives To evaluate safety of positioning and distending the functional lumen imaging probe in the pharyngo‐oesophageal segment in adults with known pharyngo‐oesophageal segment dysfunction and to obtain preliminary measurements of pharyngo‐oesophageal segment distensibility and opening during swallowing in a clinical group. Methods Prospective case series of ten adults post total laryngectomy (61–75 years) recruited from an outpatient ENT clinic. Functional lumen imaging probe was inserted trans‐nasally, and the balloon was positioned in the pharyngo‐oesophageal segment. Two 20‐mL ramp distensions were completed, and subjects performed two dry and two 5‐mL and 10‐mL liquid swallows at a 12‐mL balloon volume. Pharyngo‐oesophageal segment distensibility was calculated from cross‐sectional area (mm2) and intraballoon pressure (mmHg) measures. During swallowing, extent (mm) and duration (secs) of pharyngo‐oesophageal segment opening and intraballoon pressure drop (mmHg) were evaluated. Results Functional lumen imaging probe could be passed through the pharyngo‐oesophageal segment in seven subjects, all of whom completed the protocol. During distensions, pharyngo‐oesophageal segment cross‐sectional area increased significantly (19.47–148.3 mm2, P < 0.001), and intraballoon pressure increased significantly (15‐ to 20‐mL balloon volume, P = 0.005). Pharyngo‐oesophageal segment diameter (5.1 mm) increased during dry (7.4 mm), 5‐mL (7.3 mm) and 10‐mL (7.7 mm) liquid swallows (P = 0.018). Pharyngo‐oesophageal segment opening duration varied across dry (1 s), 5‐mL (0.8 s) and 10‐mL (1.6 s) liquid swallows. Resting intraballoon pressure (25.5 mmHg) did not alter significantly during swallowing (P = 0.656). Conclusion Functional lumen imaging probe provides novel quantitative information regarding pharyngo‐oesophageal segment distensibility and opening during swallowing in adults post total laryngectomy. No adverse events were observed in this first clinical study. Data were easy to acquire, and measures may direct candidacy for and establish effectiveness of interventions to alter pharyngo‐oesophageal segment tone.